Diskresi Tanpa Impunitas: Rekonstruksi Pertanggungjawaban Hukum Anggota Polri atas Tindakan Diskresioner di Tingkat Kepolisian Sektor - Ali Nursiswanto; Agus Rasyid Chandra Wijaya (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
Police discretion under Article 18 of Law Number 2 of 2002 grants police officers authority to take actions based on their judgment for the public interest. At the sub-district police (Polsek) level, however, this authority is exercised in direct contact with the community while receiving relatively limited supervision, creating potential risks of abuse. This study examines the implementation of police discretion at Polsek Cidadap and identifies the legal accountability mechanisms governing discretionary actions. Using normative legal research with a descriptive-analytical approach, the study applies statutory, conceptual, and case analyses supported by primary, secondary, and tertiary legal materials collected through literature and document review. Legal interpretation is conducted using grammatical, systematic, teleological, and historical methods, while qualitative analysis and deductive reasoning are employed to formulate conclusions. The findings indicate that lawful discretion must comply with legality, proportionality, accountability, human rights protection, and the principles of good governance. In practice, discretion may be exercised through conflict mediation, public order maintenance, and restorative justice. Conversely, actions exceeding authority or causing harm may result in administrative, disciplinary, ethical, civil, or criminal liability, reinforced through internal and external oversight mechanisms. The study recommends mandatory written justifications, improved documentation at the Polsek level, and clearer statutory standards for public interest and proportionality to ensure discretion promotes substantive justice while preserving legal certainty and equality before the law. The research also contributes by integrating discretion and accountability within a comprehensive framework focused on the underexplored Polsek level.